EFFECT ON PROFESSIONAL COMMITMENT JOB SATISFACTION, MOTIVATION, ORGANIZATIONAL COMMITMENT AND ETHICAL BEHAVIOR OF AUDITORS (Case Study on Public Accountants Doli, Bambang, Sudarmadji & Dada) - Irfani, Fajar; Isafaatun, SE., MM, Eliya; Magdalena SE., MM., Maria (Accounting, 2010)
The study titled The Effect of Professional Commitment on Job Satisfaction, Motivation, Organizational Commitment and Ethical Behavior Auditors, Case Study On Public Accountants Doli, Bambang, Sudarmadji & Dada, was conducted in May to June 2010. This study aims to determine the influence of auditors´ professional commitment on job satisfaction, work motivation, organizational commitment and ethical behavior of auditors. This study uses quantitative and qualitative methods of research done solely object or event described the situation in detail and depth. Data collection method used in this study are interviews and distributing a list of questions. While the methods of data analysis used in this research is descriptive analysis method and quantitative measurement method which can be expressed by the form of numbers. Based on multiple linear regression analysis with t test results can be seen that the effect on Commitment Job Satisfaction of Professional Auditors with tcount ttable 3.324 greater than 2.086. Work motivation affect the Commitment of Professional Auditors with 2.206 t value greater than t table value of 2.086. Commitment Organsiasional affect the commitment of Professional Auditors with tcount 2.099. Ethical behavior affect the Commitment of Professional Auditors with tcount greater than the value 2.090 2.086 table. F count test results can also be seen that the variable of Job Satisfaction, Work Motivation, Organizational Commitment and Ethical Behavior Auditors jointly affect the Commitment of Professional Auditors of Public Accountants Doli, Bambang, Sudarmadji & Dada with 7.186 calculated F value is greater than F table 3.492. Keywords: Auditors